2017
DOI: 10.1002/1878-0261.12059
|View full text |Cite|
|
Sign up to set email alerts
|

The prostate metastasis suppressor gene NDRG1 differentially regulates cell motility and invasion

Abstract: Experimental and clinical evidence suggests that N‐myc downregulated gene 1 (NDRG1) functions as a suppressor of prostate cancer metastasis. Elucidating pathways that drive survival and invasiveness of NDRG1‐deficient prostate cancer cells can help in designing therapeutics to target metastatic prostate cancer cells. However, the molecular mechanisms that lead NDRG1‐deficient prostate cancer cells to increased invasiveness remain largely unknown. In this study, we demonstrate that NDRG1‐deficient prostate tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 44 publications
4
44
0
Order By: Relevance
“…A recent in vitro study reported several novel eEF2K substrates; 36 among them, NDRG1 is implicated in cancer cell invasion and metastasis and was reported to be phosphorylated by eEF2K on Thr346, Thr356 and/or Thr366. [37][38][39][40] However, we were unable to detect any phosphorylation of NDRG1 by eEF2K in vitro or on the phosphorylation of NDRG1 in cells (Supporting Information Figs. S12 and S13).…”
Section: Eef2k Controls the Translation Of Mrnas Encoding Proteins Inmentioning
confidence: 86%
“…A recent in vitro study reported several novel eEF2K substrates; 36 among them, NDRG1 is implicated in cancer cell invasion and metastasis and was reported to be phosphorylated by eEF2K on Thr346, Thr356 and/or Thr366. [37][38][39][40] However, we were unable to detect any phosphorylation of NDRG1 by eEF2K in vitro or on the phosphorylation of NDRG1 in cells (Supporting Information Figs. S12 and S13).…”
Section: Eef2k Controls the Translation Of Mrnas Encoding Proteins Inmentioning
confidence: 86%
“…Additionally, overexpression of NDRG1 reduces metastasis in a rodent model of prostate cancer 49 . In contrast, prostate cancer cells with low NDRG1 expression display increased motility and invasiveness 45 , and reduced expression of NDRG1 was associated with poor overall survival in a variety of cancers, including prostate 50 . NDRG1 is transcriptionally regulated by the androgen receptor 51 .…”
Section: Ndrg1 Phosphorylation Varies In Prostate Cancer Cells and Timentioning
confidence: 98%
“…We focused on characterizing the effect of PIM1-dependent serine 330 phosphorylation (pS330) of NDRG1, given that a phosphoproteomic analyses of prostate cancer tissues by Drake et al demonstrated that levels of NDRG1 pS330 were found to be 7.7 times higher in metastatic lesions than in localized prostate cancer 43 (Sup Table 5). Although several studies have implicated NDRG1 in prostate cancer 44,45 , a link between PIM1 and NDRG1 has not been established. NDRG1 is a member of the alpha/beta hydrolase superfamily, but does not possess catalytic activity 46 .…”
Section: Ndrg1 Phosphorylation Varies In Prostate Cancer Cells and Timentioning
confidence: 99%
See 1 more Smart Citation
“…Of these molecular mechanisms, tumor suppressor genes, which normally inhibit cell growth and prevent tumor formation, become functionally inactive in cancer cells through various mechanisms in the process of tumorigenesis. Insights into the molecular function of tumor suppressors could aid in understanding pathways and barriers that prevent the process of tumor progression . Phosphatase and tensin homolog ( PTEN ), a tumor suppressor gene, is frequently mutated in a variety of human cancers including prostate cancer .…”
Section: Introductionmentioning
confidence: 99%